Exploring the role of medical imaging assistants in Australian medical imaging departments: A mixed‐methods study. Issue 1 (19th October 2022) - Pinson, Jo‐Anne; King, Olivia A.; Dennett, Amy M.; Davis, Annette; Williams, Cylie M.; Snowdon, David A.
Abstract: Introduction: Allied health assistants are support staff who assist medical imaging professionals in their clinical and non‐clinical role. Assistants can improve efficiency of medical imaging services; however, little is known about the specific tasks they perform. Method: A two‐phase explanatory, sequential mixed‐methods study design comprising a time motion survey and qualitative interviews was conducted across three health services in Victoria, Australia. Participants were medical imaging assistants supporting medical imaging professionals. Participants recorded tasks completed on a time motion proforma across two working days. Time spent on tasks was categorised into patient related and non‐patient related tasks. Semi‐structured interviews were conducted to explore assistants' perspectives about tasks, their roles and any responsibilities. Time motion data was descriptively analysed. Qualitative data were audiotaped, transcribed verbatim and analysed using the framework analysis method. Quantitative and qualitative findings were integrated using data triangulation. Results: Four medical imaging assistants participated, providing 4170 min of time motion data and 138 min of interview data. Integration of time motion and interview data revealed the medical imaging assistant role is predominantly non‐patient facing; autonomous and critical to workflow; diverse and requires flexibility; has the potential to expand into a more patient‐facing role. Conclusions: Medical imaging assistants make significant contributions to workflow management. Their role is predominantly non‐patient facing but there appear opportunities for the clinical role to expand. Realizing these opportunities will require careful consideration of the challenges and benefits of extending their scope of practice. Abstract : Little is known about the role and responsibilities of Australian medical imaging assistants. A two‐phase explanatory mixed methods study comprising a time motion survey and qualitative interviews were conducted to determine the tasks performed, time spent and explore the medical imaging assistants' perspective of their roles. Medical imaging assistants make significant contributions to workflow management, with their role predominantly non‐patient facing.